Pantai Taman-Pacitan ecotourism development: Conservation and community empowerment orientation - Prihanta, Wahyu; Zainuri, Ach. Muhib; Hartini, Rahayu; Syarifuddin, Amir; Patma, Tundung Subali (Universitas Muhammadiyah Malang, 2020)
Ecotourism is a form of tourism that is closely linked to the principle of conservation. Thus, ecotourism is right and beneficial in maintaining the integrity and authenticity of ecosystems in natural areas, particularly turtle conservation areas. Ecotourism is synergized to turtle conservation as it has such features: (1) Conservation, the use of biodiversity does not damage the natural source, also it does not cause negative impact whereas it is very environmentally friendly, (2) Education, by improving communityâ€™s awareness and changing their behavior about the need for conservation of living natural resources and their conservation, (3) Economy, ecotourism provides economic benefits and spur regional development; and (4) Active role of community, this is done by building partnership with local communities for the development of ecotourism. Based on the issues, â€œIbW Conservation and Ecotourism NgadirojoÂ District Pacitan Regionâ€ was done by (1) Making a model of tourism activities that is environmentally, ecologically, socially, and economically beneficial to local communities and to the sustainability of natural resources, (2) Assessing the object of tourist attraction in flora and fauna conservation areas, in this case sea turtles and their ecosystems, so that can synergize with ecotourism activities, and (3) Making a model of local community-based tourist institution. The method implemented to achieve the objectives was â€œCommunity Empowerment through Ecotourismâ€ which is described as follow: (1) Land Conservation, value and travel product, (2) Creation of an ecotourism atmosphere that all people who live in the area will gain the benefit, (3) The development of tourism activities that carry the excellence of the physical, economic, socio-cultural aspects of the local, (4) The solid image of ecotourism activities in the region that is supported by the readiness of all stakeholders, and (5) Integration of turtle theme conservation and ecotourism area with other supporting tourism products in the Regency. Pacitan Construction of facilities that have been carried out are: (1) developing the forest of eternity, (2) ecological restoration of coastal forests, (3) making sea water wells for turtle ponds, (4) nursery of coastal forest vegetation, (5) construction of marine biota ponds and sanitation facilities, (6) construction of shelters and gazebos, (7) construction of parking lot, and (8) widening of the ecotourism ring road. The next stage plans are: (1) ecotourism community empowerment, (2) strengthening the ecotourism area, and (3) revitalization of marine biota ponds.